2014
DOI: 10.1590/1983-084x/12_155
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity using medicinal plant extracts against pathogens of coffee tree

Abstract: Generally, the medicinal plants have antifungal substances that can be used for the plant protection against phytopathogens. The objective of this study was to know the efficiency of aqueous extracts from medicinal plants against the major etiological agents of coffee tree. The aqueous extracts used were extracted from bulbs of Allium sativum, leaves of Vernonia polysphaera, Cymbopogon citratus, Cymbopogon nardus, Cordia verbenacea, Eucalyptus citriodora, Ricinus communis, Azadirachta indica, Piper hispidinerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 10 publications
1
27
0
9
Order By: Relevance
“…Antifungal analysis of A. sativum extracts against different fungal pathogens of coffee tree shows that the A. ampeloprasum extracts can inhibit mycelial growth by 100% as well as also effectively preventing the germination of spores [4]. It is found that the mechanism of action, of A. ampeloprasum as an antifungal agent, is due to the competitive inhibition of sulfhydryl-containing enzymes by allicin and the inhibition of lipid biosynthesis leading to cell wall damage, as seen in the case of Candida albicans [9,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antifungal analysis of A. sativum extracts against different fungal pathogens of coffee tree shows that the A. ampeloprasum extracts can inhibit mycelial growth by 100% as well as also effectively preventing the germination of spores [4]. It is found that the mechanism of action, of A. ampeloprasum as an antifungal agent, is due to the competitive inhibition of sulfhydryl-containing enzymes by allicin and the inhibition of lipid biosynthesis leading to cell wall damage, as seen in the case of Candida albicans [9,21].…”
Section: Discussionmentioning
confidence: 99%
“…Many natural products obtained from plants having biocidal activity are considered as an alternate effective and eco-friendly source against phytopathogens [3]. Moreover, these natural products are usually cheaper than commercial fungicides and are easily accessible to farmers [4]. Allium species is recognized as an important genus of the Alliaceae family and well known for its biocidal properties [5].…”
Section: Introductionmentioning
confidence: 99%
“…), a menta (Mentha piperita L.) (Carnelossi et al, 2009;Sarmento-Brum et al, 2014;Bhuyan, et al, 2015), e o cravo da índia (Syzygium aromaticum (L.) Merr. & L. M. Perry) (Silva et al, 2014).…”
Section: Introductionunclassified
“…A inibição do crescimento dos fungos fitopatogênicos, por estes antimicrobianos naturais é devido às substâncias bioativas encontradas em plantas (Chiejina & Ukeh, 2012, Silva et al, 2014 (Ogbebor et al, 2007 A concentração inibitória mínima (CIM) dos óleos essenciais foi determinada seguindo os protocolos do CLSI (2008), utilizando-se o método de microdiluição em placas. Após incubação a 37ºC por cinco dias a CIM foi avaliada, sendo que a presença de células fúngicas viáveis nas concentrações não inibitórias foi determinada pela adição, em cada amostra, do corante 2,3,5 -Triphenyltetrazolium Chloride , no volume de 50 µL.…”
Section: Introductionunclassified
“…However, the plead for sustainable agriculture in an eco-friendly manner cannot be sustained with such health hazard chemicals (Oruc, 2010). An alternative strategy could be applied through the exploration of natural antimicrobial compounds from plant bark, stems, leaves, flowers and fruits (Ikram and Dawar, 2013;Silva et al, 2014;Javaid and Akhtar, 2015). These can act directly as pesticides or may provide structural lead for the development of pesticides (Kilani, 2006;Tapwal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%